Fiscal Adjustment in EU Countries : A Balance Sheet Approach - Moriyama, Kenji; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 2004)
Several European Union countries have recently implemented or are envisaging fiscal that operations improve budgetary figures but have no structural impact on government finances. This paper evaluates some of these measures using a balance sheet approach. In particular, it examines the degree to which reductions in government debt in EU countries has been accompanied by a decumulation of government assets. In the run-up to Maastricht (1997) it finds a strong correlation between changes in government liabilities and government assets, and larger declines in government assets in countries starting from higher public debt levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet